Ternary transition metal boride coating as well as preparation method and application thereof

The preparation of ternary transition metal boride coatings by using molten salt in reaction and electric field-induced nanoassembly technology in a high-temperature resistance furnace is solved, and the preparation of low-cost, fully dense and high binding strength is achieved.

CN119660757AActive Publication Date: 2025-03-21ANHUI UNIVERSITY OF TECHNOLOGY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411903116.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-21
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

The existing ternary transition metal boride coating preparation methods have problems such as high cost, low production efficiency, poor density and complex equipment, which limits its application scope.

Method used

Molten salts containing ternary transition metal boride nanoparticles were prepared by reaction in molten salts, and a ternary transition metal boride coating was prepared in a high-temperature resistance furnace through electric field-induced nanoassembly technology.

Benefits of technology

The ternary transition metal boride coating with low cost is achieved, which simplifies the process flow and reduces the cost of equipment without the need for surface pretreatment of the matrix material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119660757A_ABST
    Figure CN119660757A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of surface coating preparation, in particular to a ternary transition metal boride coating and a preparation method and application thereof.The preparation method comprises the steps that transition metal oxide powder, a boron source, inorganic salt and a nanoparticle surfactant are evenly mixed and heated to 1000-1200 DEG C, and fused salt containing ternary transition metal boride nanoparticles is obtained after full reaction; a graphite positive electrode and a negative electrode to be deposited are inserted into fused salt containing ternary transition metal boride nano-particles, after the electric field intensity of 0.3 V / cm-0. 7V / cm is applied, the ternary transition metal boride nano-particles in the fused salt are assembled on the surface of the negative electrode under the action of an electric field to form the (M < x > N1-x) B2 ternary transition metal boride coating, M and N are independently selected from any one of zirconium, hafnium, niobium and tantalum, and the thickness of the (M < x > N1-x) B2 ternary transition metal boride coating is smaller than or equal to 0.5 mm. And x ranges from 0.1 to 0.9. The ternary transition metal boride coating which is fully compact and high in bonding strength is prepared, the equipment cost is low, and the technological operation is simple and convenient.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of surface coating preparation, and in particular to a ternary transition metal boride coating, a preparation method and application thereof. Background Art

[0002] Ternary transition metal boride coatings are highly favored in the industrial field due to their excellent performance, and have great potential application value in the fields of chemical industry, metallurgy, marine engineering, and aerospace. Ternary transition metal borides have high melting point, high hardness, good wear resistance and corrosion resistance, and excellent high-temperature oxidation resistance. They can be used to improve the corrosion resistance of steel, improve the wear resistance of titanium metal materials, or improve the high-temperature oxidation resistance of carbon-based materials. The excellent properties of ternary transition metal borides make them ideal coating materials for protecting substrates in harsh application environments, especially in applications where materials are required to be wear-resistant, corrosion-resistant, and stable at high temperatures.

[0003] At present, the preparation methods of ternary transition metal boride coatings mainly include laser cladding, plasma spraying, chemical vapor deposition, etc. Laser cladding is favored for its high precision and good metallurgical bonding, but it has shortcomings such as high cost, low production efficiency, and poor coating density. Plasma spraying can achieve a high deposition rate, but there is a problem of high porosity, which in turn affects the bonding strength between the coating and the substrate. The coating prepared by chemical vapor deposition is uniform and dense, but the equipment is complex, the cost is high, and the environmental conditions are strict. The problems existing in the existing coating preparation methods have severely limited the application scope of ternary transition metal boride coatings with excellent performance. It is necessary to improve the existing preparation process or develop a new coating preparation method to achieve low-cost preparation of high-quality ternary transition metal boride coatings.

[0004] In view of the above-mentioned defects, the inventors of the present invention finally obtained the present invention after a long period of research and practice. Summary of the invention

[0005] The purpose of the present invention is to solve the problem of how to prepare a fully dense ternary transition metal boride coating with excellent bonding strength at low cost, and to provide a ternary transition metal boride coating, a preparation method and an application thereof.

[0006] In order to achieve the above object, the present invention discloses a method for preparing a ternary transition metal boride coating, comprising the following steps:

[0007] S1, preparing molten salt containing ternary transition metal boride nanoparticles by reaction in molten salt:

[0008] The transition metal oxide powder, boron source, inorganic salt and nanoparticle surfactant are mixed and heated to 1000°C to 1200°C, and after reaction, a molten salt containing ternary transition metal boride nanoparticles is obtained, and the nanoparticle size is 20nm to 100nm;

[0009] S2, Preparation of ternary transition metal boride coatings by electric field induced nanoassembly in molten salt containing nanoparticles:

[0010] A graphite positive electrode and a negative electrode to be deposited are inserted into a molten salt containing ternary transition metal boride nanoparticles. After an electric field is applied, the ternary transition metal boride nanoparticles in the molten salt assemble on the surface of the negative electrode under the action of the electric field to form a ternary transition metal boride coating.

[0011] In the step S1, the transition metal oxide is any two of ZrO2, HfO2, Nb2O5 and Ta2O5, and its particle size is 50nm to 200nm and its purity is 99.9%.

[0012] In the step S1, the boron source is boron powder or boron carbide powder, the particle size of which is 0.5 μm to 2 μm and the purity is 99.9%.

[0013] In step S1, the inorganic salt is NaCl-KCl-MgCl2 or NaF-AlF3, and the purity is analytically pure. In the NaCl-KCl-MgCl2, the molar ratio of NaCl to KCl is 1:1, and the content of MgCl2 is 10wt% to 60wt%; the content of AlF3 in the NaF-AlF3 is 30wt% to 70wt%.

[0014] In the step S1, the nanoparticle surfactant is any one or two of Cr2O3, P2O5, Al2O3 and Fe2O3, and the purity is 99.9%.

[0015] In step S1, the molar ratio of the boron source to the transition metal oxide powder is 2:1 to 9:1, the total amount of inorganic salt added is 25 to 40 times the total mass of the transition metal oxide powder and the boron source, and the nanoparticle surfactant is 1% to 2% of the total weight of the transition metal oxide, boron powder and inorganic salt.

[0016] In the step S2, the material of the negative electrode to be deposited is any one of low carbon steel, titanium and titanium alloys, molybdenum and molybdenum alloys, graphite and C / C composite materials.

[0017] In step S2, the intensity of the applied electric field is 0.3 V / cm to 0.7 V / cm, and the corresponding voltage is less than the theoretical precipitation voltage of the electroactive material in the molten salt.

[0018] In step S2, the chemical formula of the ternary transition metal boride coating is (M x N1-x )B2, wherein, M and N are independently selected from any one of zirconium, hafnium, niobium and tantalum, and x ranges from 0.1 to 0.9.

[0019] The invention also discloses a ternary transition metal boride coating prepared by the preparation method and application of the ternary transition metal boride coating in protecting substrates in harsh environments.

[0020] For the ternary transition metal boride coating prepared by electric field induced nanoassembly using the NaCl-KCl-MgCl2 molten salt system, after the coating sample is taken out from the molten salt, it is immersed in deionized water for 20min to 40min, and then immersed in acetone for 5min to 10min to remove water, and then dried for use. For the ternary transition metal boride coating prepared by electric field induced nanoassembly using the NaF-AlF3 molten salt system, after the coating sample is taken out from the molten salt, it is immersed in molten NaCl-KCl at 650℃ to 700℃ for 5min to 10min to remove the solid salt residue on the surface of the coating. Then the coating sample is immersed in deionized water for 20 to 40min, and then immersed in acetone for 5min to 10min to remove water, and then dried for use.

[0021] Compared with the prior art, the beneficial effects of the present invention are:

[0022] 1. The present invention adopts a common high-temperature resistance furnace to prepare the ternary transition metal boride coating, and its equipment cost is low compared with the existing preparation method;

[0023] 2. The present invention realizes the preparation of ternary transition metal boride nanoparticles and coatings simultaneously in a high-temperature resistance furnace, which makes the process short and easy to operate;

[0024] 3. The present invention uses transition metal oxides and boron powder as precursors to synthesize ternary transition metal boride nanoparticles in situ in molten salt, which can effectively reduce the raw material cost of preparing the ternary transition metal boride coating;

[0025] 4. The molten salt medium used in the present invention has a purifying effect on the surface of substrate materials such as low-carbon steel, titanium metal and graphite. Before coating preparation, there is no need to perform surface pretreatment such as grinding on the surface of the substrate material. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 For nano-(Hf 0.5 Zr 0.5 ) XRD test results of NaF-AlF3 salt of B2;

[0027] Figure 2 Nano-Hf 0.5 Zr 0.5) SEM analysis of B2;

[0028] Figure 3 Preparation of graphite anode substrate (Hf 0.5 Zr 0.5 ) XRD analysis of B2 coating;

[0029] Figure 4 Preparation of graphite anode substrate (Hf 0.5 Zr 0.5 )B2 coating cross-sectional appearance;

[0030] Figure 5 On the graphite negative electrode substrate (Hf 0.5 Zr 0.5 )B2 coating cross-section mapping;

[0031] Figure 6 Preparation of graphite anode substrate (Hf 0.5 Zr 0.5 ) SEM image of the cross section of B2 coating;

[0032] Figure 7 =Hf 0.5 Zr 0.5 ) Dynamic oxidation test results of B2 coating in air at room temperature to 1500℃. DETAILED DESCRIPTION

[0033] The above and other technical features and advantages of the present invention are described in more detail below in conjunction with the accompanying drawings.

[0034] Example 1

[0035] Boron powder (average particle size 0.6 μm), zirconium dioxide powder (average particle size 100 nm) and hafnium dioxide powder (average particle size 150 nm) are mixed in a molar ratio of 5:0.5:0.5. The solid inorganic salt is a mixed salt of sodium fluoride and aluminum fluoride in a molar ratio of 1:1. The nanoparticle surfactant is aluminum oxide, and the addition amount is 2wt% of the total weight of transition metal oxides, boron powder and inorganic salts. After mixing all the above raw materials in a mortar and grinding for 15 minutes, all are added to a graphite crucible. Then the graphite crucible is placed in an argon-protected resistance furnace and heated to 1050°C, kept warm for 3 hours to form (Hf 0.5 Zr 0.5)B2 nanoparticles are stably suspended in the molten salt, and the particle size of the nanoparticles is 60nm to 120nm. Then, the graphite positive electrode and the graphite negative electrode are inserted into the NaF-AlF3 molten salt containing the nanoparticles, the electric field strength is selected to be 0.5V / cm, the corresponding voltage is 1.2V, and the electric field is turned on to induce the nano-assembly. After applying the voltage for 60 minutes, the power is turned off and the (Hf 0.5 Zr 0.5 The graphite anode with the B2 coating was taken out and immersed in molten NaCl-KCl at 680°C for 8 min to remove the solid salt residue on the coating surface. 0.5 Zr 0.5 The graphite anode with B2 coating was immersed in deionized water for 25 min, then immersed in acetone for 6 min to remove water, and dried to obtain a dense (Hf 0.5 Zr 0.5 )B2 coating.

[0036] Figure 1 and Figure 2 They are respectively dipped, cooled and washed with water containing nano (Hf 0.5 Zr 0.5 )XRD and SEM test analysis results of NaF-AlF3 salt of B2. Figure 1 and Figure 2 It shows that nano (Hf 0.5 Zr 0.5 )B2 particles, the particle size of which is 60 to 120 nm. Figure 3 For the prepared graphite negative electrode (Hf 0.5 Zr 0.5 )B2 coating XRD analysis results, which shows that the electric field induced nanoassembly in the molten salt has obtained (Hf 0.5 Zr 0.5 )B2 coating.

[0037] Figure 4 and Figure 5 On the graphite negative electrode (Hf 0.5 Zr 0.5 )B2 coating cross-section appearance diagram and corresponding mapping test diagram. Figure 4 and Figure 5 It can be seen that the coating can completely cover the coating surface, the coating thickness is basically uniform, and the Zr and Hf elements in the coating are evenly distributed.

[0038] Figure 6 For the prepared (Hf 0.5 Zr 0.5 ) SEM image of B2 coating. From this image, it can be seen that as the coating structure is gradually magnified, it can be observed that the coating is a fully dense coating without pores.

[0039] Figure 7 =Hf 0.5 Zr 0.5 ) Dynamic oxidation test results of B2 coating in air from room temperature to 1500℃. Below 600℃, the mass of the coating remains relatively stable, indicating that the coating is hardly oxidized. Starting from 600℃, the weight of the coating begins to increase, indicating that the coating reacts with oxygen to form an oxide solid solution containing HfO2 and ZrO2, which protects the substrate from oxidation.

[0040] Example 2

[0041] Boron powder (average particle size 1 μm), niobium pentoxide powder (average particle size 120 nm) and hafnium dioxide powder (average particle size 150 nm) are mixed in a molar ratio of 6:0.5:1. The solid inorganic salt is a mixed salt of sodium chloride, potassium chloride and magnesium chloride in a molar ratio of 1:1:0.3. The nanoparticle surfactant is chromium trioxide, and the added amount is 1.5wt% of the total weight of transition metal oxides, boron powder and inorganic salts. All the above raw materials are mixed in a mortar and ground for 12 minutes, and then all are added to a graphite crucible. The graphite crucible is then placed in an argon-protected resistance furnace and heated to 1100°C, kept warm for 4 hours to form (Hf 0.67 Nb 0.33 )B2 nanoparticles are stably suspended in the molten salt, and the particle size of the nanoparticles is 80nm to 110nm. Then, a graphite positive electrode and an industrial pure titanium negative electrode are inserted into the NaCl-KCl-MgCl2 molten salt containing nanoparticles. The electric field strength is selected to be 0.55V / cm, and the corresponding voltage is 1.1V. The electric field is turned on to induce nanoassembly. After applying the voltage for 40 minutes, the power is turned off and the (Hf 0.67 Nb 0.33 ) B2 coated industrial pure titanium negative electrode was taken out and immersed in deionized water for 30 minutes, then immersed in acetone for 7 minutes to remove water, and dried to obtain a dense (Hf 0.67 Nb 0.33 )B2 coating.

[0042] Example 3

[0043] Boron carbide powder (average particle size 1.2μm), niobium pentoxide powder (average particle size 110nm) and tantalum pentoxide powder (average particle size 130nm) are mixed in a molar ratio of 2:0.5:0.5. The solid inorganic salt is a mixed salt of sodium fluoride and aluminum fluoride in a molar ratio of 1.2:1. The nanoparticle surfactant is ferric oxide, and the added amount is 1.6wt% of the total weight of transition metal oxides, boron carbide powder and inorganic salts. All the above raw materials are mixed in a mortar and ground for 20 minutes, and then all are added to a graphite crucible. The graphite crucible is then placed in an argon-protected resistance furnace and heated to 1020°C, and kept warm for 5 hours to form (Nb 0.5 Ta 0.5 )B2 nanoparticles are stably suspended in the molten salt, and the particle size of the nanoparticles is 80nm to 120nm. Then, a graphite positive electrode and a metal molybdenum negative electrode are inserted into the NaF-AlF3 molten salt containing nanoparticles, and the electric field strength is selected to be 0.6V / cm, and the corresponding voltage is 1.0V. The electric field is turned on to induce nanoassembly. After applying the voltage for 70 minutes, the power is turned off and the (Nb 0.5 Ta 0.5 The metal molybdenum negative electrode with the )B2 coating was taken out and immersed in molten NaCl-KCl at 690°C for 7 minutes to remove the solid salt residue on the coating surface. 0.5 Ta 0.5 The metal molybdenum negative electrode with )B2 coating was immersed in deionized water for 30 minutes, then immersed in acetone for 8 minutes to remove water, and dried to obtain a dense (Nb 0.5 Ta 0.5 )B2 coating.

[0044] The above description is only a preferred embodiment of the present invention, which is only illustrative and not restrictive of the present invention. Those skilled in the art understand that many changes, modifications, and even equivalences may be made to the present invention within the spirit and scope defined by the claims of the present invention, but all of them will fall within the scope of protection of the present invention.

Claims

1. A method for preparing a ternary transition metal boride coating, characterized in that: The following steps are involved: S1, preparing molten salt containing ternary transition metal boride nanoparticles by reaction in molten salt: The transition metal oxide powder, boron source, inorganic salt and nanoparticle surfactant are mixed and heated to 1000°C to 1200°C, and after reaction, a molten salt containing ternary transition metal boride nanoparticles is obtained, and the nanoparticle size is 20nm to 100nm; S2, Preparation of ternary transition metal boride coatings by electric field induced nanoassembly in molten salt containing nanoparticles: A graphite positive electrode and a negative electrode to be deposited are inserted into a molten salt containing ternary transition metal boride nanoparticles. After an electric field is applied, the ternary transition metal boride nanoparticles in the molten salt assemble on the surface of the negative electrode under the action of the electric field to form a ternary transition metal boride coating.

2. The method for preparing a ternary transition metal boride coating according to claim 1, characterized in that: In the step S1, the transition metal oxide is any two of ZrO2, HfO2, Nb2O5 and Ta2O5, and its particle size is 50nm to 200nm and its purity is 99.9%.

3. The method for preparing a ternary transition metal boride coating according to claim 1, characterized in that: In the step S1, the boron source is boron powder or boron carbide powder, the particle size of which is 0.5 μm to 2 μm and the purity is 99.9%.

4. The method for preparing a ternary transition metal boride coating according to claim 1, characterized in that: In step S1, the inorganic salt is NaCl-KCl-MgCl2 or NaF-AlF3, and the purity is analytically pure. In the NaCl-KCl-MgCl2, the molar ratio of NaCl to KCl is 1:1, and the content of MgCl2 is 10wt% to 60wt%; the content of AlF3 in the NaF-AlF3 is 30wt% to 70wt%.

5. The method for preparing a ternary transition metal boride coating according to claim 1, characterized in that: In the step S1, the nanoparticle surfactant is any one or two of Cr2O3, P2O5, Al2O3 and Fe2O3, and the purity is 99.9%.

6. The method for preparing a ternary transition metal boride coating according to claim 1, characterized in that: In step S1, the molar ratio of the boron source to the transition metal oxide powder is 2:1 to 9:1, the total amount of inorganic salt added is 25 to 40 times the total mass of the transition metal oxide powder and the boron source, and the nanoparticle surfactant is 1% to 2wt% of the total weight of the transition metal oxide, boron powder and inorganic salt.

7. The method for preparing a ternary transition metal boride coating according to claim 1, characterized in that: In the step S2, the material of the negative electrode to be deposited is any one of low carbon steel, titanium and titanium alloys, molybdenum and molybdenum alloys, graphite and C / C composite materials.

8. The method for preparing a ternary transition metal boride coating according to claim 1, characterized in that: In step S2, the intensity of the applied electric field is 0.3 V / cm to 0.7 V / cm, and the corresponding voltage is less than the theoretical precipitation voltage of the electroactive material in the molten salt.

9. A ternary transition metal boride coating prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The chemical formula of the ternary transition metal boride coating is (M x N 1-x )B2, wherein M and N are independently selected from any one of zirconium, hafnium, niobium and tantalum, and x ranges from 0.1 to 0.

9.

10. Use of the ternary transition metal boride coating as claimed in claim 9 in protecting substrates in harsh environments.

Citation Information

Patent Citations

  • Deposition and thermal diffusion of borides and carbides of refractory metals

    CA2330982A1

  • Method for coating surfaces and use of the objects coated using said method

    CN103209774A

  • Method for preparing transition metal boride coating through fused salt in-situ synthesis and electrophoretic deposition

    CN114045546A

  • Room-temperature ferromagnetic semiconductor and preparation method and application thereof

    CN114506851A

  • Transition metal boride, preparation method and application thereof

    CN117985729A